A systematic review on nano-delivery systems enriched with aromatic compounds: Flavor, odor, and chemical quality perspectives in fish - Turgay Cetinkaya; Mehmet Turan Ayseli (Food Chemistry Advances)
The distinct fishy odors found in fish products are mainly linked to the surrounding environment (eg, algae, water, and feed). These odor compounds can be intensified during processing and storage as a result of lipid autoxidation, enzymatic reactions, degradation of TMAO, and Strecker degradation. For this purpose, the area of nanoapplication methods is attracting attention because of their potential to play a crucial role in maintaining the quality and odor properties of fish, allowing the inhibition of the formation of unpleasant volatile compounds through the oxidation of aroma precursors, such as fatty acids. The nanofibers and NPs the allow carrying fragrances and flavors, resulting in improved performance of the EOs or masking unpleasant volatile compounds that are generated through lipid oxidation. Furthermore, nanovesicles containing aroma and flavor compounds from EOs and microalgae can extend the chemical decomposition with nanocoating methods. The combination of nanomaterials could be one of the promising ways to mask bitter taste and off-odor and delay spoilage in fish products as future trends. In this systematic review, the applications of nanotechnology in recent papers published over the last 10 years related to chemical quality and odor were discussed.